Caracterização fotofísica da sonda fluorescente 6-OH-BTA-0 e sua interação com peptídeos beta amiloide - Souza, Marcele Silva de (2021)
The present work studied the interaction of different forms of the beta amyloid peptide Aβ-42 (monomer, oligomer and fibril) with the fluorescent molecule 2- (4-aminophenyl) -1,3-benzothiazole-6-ol (6-OH-BTA -0). The pure 6-OH-BTA molecule was characterized in relation to its fluorescent properties in different solvents. The production of the different oligomeric conformations of the beta amyloid peptide were evaluated for purity and morphological dispersion, using the techniques of high-performance liquid chromatography by size exclusion (SEC-HPLC), electrophoresis in polyacrylamide gels (SDS-PAGE), microscopy atomic force (AFM) and transmission electron microscopy (TEM). The study of the interaction of the 6-OH-BTA-0 molecule with the different forms of the amyloid beta peptide (monomer, oligomer and fibril) was carried out by titrating the 6-OH-BTA-0 molecule at 500 nM, varying the concentrations of the different conformations of Aβ-42 (33.22 to 435 nM), as well as temperature (25, 37 and 42 ° C). An intrinsic fluorescence with a bathochromic shift in the fluorescence spectrum was observed in the 6-OH-BTA-0 molecule according to the polarity variation and solvent dielectric constant. The different formulations of the peptide presented aggregation structures with variable sizes, reaching hundreds of nanometers in length in the case of fibrils and 1-6 nm in diameter. In general, the monomeric form has a greater content of more spherical aggregates and the fibril form, a greater content of fibrillar and highly compacted structures. In the study of interaction by fluorescence, a moderate quenching of the fluorescence of the 6-OH-BTA-0 molecule was observed due to the presence of the different Aβ-42 conformations. In the forms of oligomer and fibril it was possible to observe a static quenching by the formation of a complex without the dependence of temperature, the values of the Stern-Volmer affinity constants at temperatures of 25 ° C, 37 ° C and 42 ° C, respectively, in the oligomeric form it was 80.0 ± 12.5, 48.4 ± 3.9 and 42.3 ± 2.2, and in the fibrillar form it was 64,0 ± 7,4, 55,3 ± 4,1 e 33,7 ± 4,3 in monomeric form it was already possible to observe the influence of temperature showing a dynamic quenching, the Stern-Volmer constants found were 70.3 ± 5.2, 35.1 ± 5.8 and 75, 4 ± 18.9.